Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №96

Представьте в виде дроби:
а)
$\frac{4}{y + 2} - \frac{3}{y - 2} + \frac{12}{y^2 - 4}$
;
б)
$\frac{a}{a - 6} - \frac{3}{a + 6} + \frac{a^2}{36 - a^2}$
;
в)
$\frac{x^2}{(x - y)^2} - \frac{x + y}{2x - 2y}$
;
г)
$\frac{b}{(a - b)^2} - \frac{a + b}{b^2 - ab}$
.

Решение а

$\frac{4}{y + 2} - \frac{3}{y - 2} + \frac{12}{y^2 - 4} = \frac{4(y - 2) - 3(y + 2) + 12}{(y + 2)(y - 2)} = \frac{y - 2}{(y + 2)(y - 2)} = \frac{1}{y + 2}$

Решение б

$\frac{a}{a - 6} - \frac{3}{a + 6} + \frac{a^2}{36 - a^2} = \frac{a(a + 6) - 3(a - 6) - a^2}{(a - 6)(a + 6)} = \frac{a^2 + 6a - 3a + 18 - a^2}{(a - 6)(a + 6)} = \frac{3(a + 6)}{(a - 6)(a+ 6)} = \frac{3}{a - 6}$

Решение в

$\frac{x^2}{(x - y)^2} - \frac{x + y}{2x - 2y} = \frac{2x^2 - (x + y)(x - y)}{2(x - y)^2} = \frac{x^2 + y^2}{2(x - y)^2}$

Решение г

$\frac{b}{(a - b)^2} - \frac{a + b}{b^2 - ab} = \frac{b}{(a - b)^2} + \frac{a + b}{b(a - b)} = \frac{b^2 + (a + b)(a - b)}{b(a - b)^2} = \frac{a^2}{b(a - b)^2}$